Discovering John : content, interpretation, reception - Edwards, Ruth B. (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2015)
In this student-friendly introduction to the Gospel of John, Ruth B. Edwards illuminates the biblical text's content, interpretation, and historical reception. What is the purpose of John's Gospel? How does John relate to the religious thought of its day? What is distinctive about its message? How does it speak to our world today? Is it anti-Semitic? Edwards expertly guides readers through such questions, helping those interested in this provocative, sometimes enigmatic Gospel to discover the answers for themselves. (Back cover).
Introduction -- Interpreting John: strategies for reading -- The question of authorship -- Traditions, sources and relation to the 'historical Jesus' -- Purpose, audience, place and date of composition -- Jesus' miracles as narrative theology -- Christological confessions and titles for Jesus -- Jesus' passion and resurrection -- Jesus: Word incarnate and Father's son -- Characters in John's story -- 'Anti-Semitism'/'anti-Judaism' in John's gospel? -- 'Replacement theology' and Jewish monotheism -- Conclusions: the value of John's gospel today.
Includes bibliographical references (pages 206-237) and index.
Keywords: Bible. -- Criticism, interpretation, etc